ANALISIS EFEKTIVITAS PENDEKATAN KEPADA MASYARAKAT DALAM STRATEGI KEMENANGAN MUHAMMAD AZIS DALAM PEMILIHAN DPRD TANGERANG SELATAN - Putri Darajat, Kirana; Fajriyyah Angeline, Alika; Descayu Sagita, Avia; Larasati Tupen, Devita; Adzzahra, Chalisha; Prakoso Aji, Muhammad (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2024)
This research discusses Muhammad Azis's political communication strategy in the campaign for the election of South Tangerang DPRD members. The focus is on the use of digital technology, such as WhatsApp Blast and social media, combined with traditional campaign methods. With this approach, Azis managed to reach more people while building closer relationships through direct meetings. This research reviews the advantages and disadvantages of these strategies and emphasizes the importance of political communication in influencing public opinion and voter decisions. The results show that the combination of online campaigning and face-to-face interaction is an effective and complementary tool in the context of local politics. This study uses a qualitative approach to explore the impact of these strategies on the success of Azis' campaign.